(3OjhGf YHOGddg Hf MeRIs - (3GdefUhQ HGddg (B- (3GdefUhQ , YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI Gdjefj, GdRjOj GdefUhQ HGddg,J (B614 (3g` s
(3ChdgG (B:s
(3ef HGH GdEaJNGQ(B: (3bGdJ CejeI hgj dG JOQj LgdkG Hcfg YhGbH GdOgQ s
(3BNQgG (B:s
(3ef HGH GdehGYX hGdBOGH, hgh GdHGH GdKGef(B: (3hoLO dj HYahc jG ef jLd ef Cf jMjW Hg ef jUa s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdChQGb GdCNjQI ef GdeNWhW HNW eZGjQs
(3hocJHJ SfI (B894(3g```s
(3hHBNQgG ebGHdI Ydi fSNI HBNQgG bQGAI SfI (B633 (3heQJHI Ydi GdCZQGVs
(3hHGdfSNI BKGQ JbWjY s
(3GfXQ CjVkG OjhGf hdOg eMeO Hf YHOGddg Hf MeRI s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs